MANAJEMEN FINANSIAL PENDIDIKAN ISLAM DI FATONI UNIVERSITY THAILAND - Abdulroman Mahir; Fachruddin Azmi; Syafaruddin Syafaruddin (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
This study aims to analyze the financial planning of Islamic education at Fatoni University Thailand. Then describe the financial organization of Islamic education at Fatoni University Thailand. Then to describe the implementation of Islamic education financial resources at Fatoni University Thailand. Then to describe the supervision of the Islamic education financial program at Fatoni University Thailand. Lastly, to describe the evaluation of the use of Islamic education finance at Fatoni University Thailand. This research is qualitative. The process of extracting data holistically, either by means of in-depth interviews with a series of questions, observations in the form of observations, and collection of documents with the aim of obtaining correct and valid data related to the research theme. There are 5 (five) findings that became the results of this study, namely: Financial planning for Islamic education at Fatoni University Thailand in the construction of lecture buildings maximizes assistance from IDB waqf costs. Financial Organization of Islamic Education at Fatoni University Thailand through the structure. The implementation of Islamic education financial resources at Fatoni University Thailand is by utilizing waqf funds. The supervision of the Islamic education financial program at Fatoni University Thailand is carried out by the Ministry of Higher Education, Science and Evaluation. Financial evaluation of Islamic education at Fatoni University Thailand that monthly financial reports are made.